The Effect of special Exercises Using Interval Training To Develop Maximum Speed and Its Relationship with Psychological Endurance Strength In Advance Road Cyclists - Hassan, Taraq (Journal of Physical Education, 2016)
The aim of the research is to prepare special exercises using interval training to develop maximum speed in advance road cyclists and to identify the effect of these exercises on Maximum speed development. In addition to that, the research aims at identifying the relationship between maximal speed and the Strength of psychological endurance in advance road cyclists. The subjects were (8) cyclists of one group that was pre & post tested. In The training session Special exercises similar to that of the pretests were given. The Training program consisted of (16) training Session with two sessions per week for eight weeks. Kamil Abood’s scale was distributed to measure the strength of psychological endurance after the posttest. The Most important conclusions were that special exercises similar to the skills during competition improve maximum Speed development. Finally the researcher concluded that there is a relationship between maximum strength and psychological endurance strength.